Isolation and identification of mold and yeast in medombae, a rice wine starter culture from Kompong Cham Province, Cambodia - Chay, C.,; Dizon, E.I.,; Elegado, F.B.; Norng, C.; Hurtada, W.A.; Raymundo, L.C. (Food Research, 2017)
Medombae is a dried starter culture used for traditional rice wine processing in Cambodia. However, studies on the role of mold and yeast present and their efficacy for rice wine fermentation are still limited. Cultural and morphological tests revealed that the isolated representative mold strains were isolated based on the method of identification used as Mucor spp and Rhizopus oryzae. On the other hand, the biochemical properties of the first yeast isolate using the Vitek 2 identification system and YST Card identification suggests its identity as Candida tropicalis. The second yeast strain examined for its morphological and cultural characteristic using agar slide technique, and its protein profile which was compared to the reference and sample protein masses using Biomerieux Vitek MS (MALD-TOF) showed the presence of Saccharomyces cerevisiae. The biochemical characteristics and cellular characteristics of the third yeast isolate as described by Lodder (1970) and Kreger-Van Rij (1984) confirmed its identity as Saccharomycopsis spp. The DNA test of identification of the isolates should be conducted to further confirm the identity of the isolates.